Using weather index insurance to improve drought response for famine prevention - Chantarat, S.; Barrett, Christopher B.; Mude, Andrew G.; Turvey, C.G. (Wiley, 2007)
There is a strong link between weather and the welfare of poor populations. Low-frequency, short-term, but catastrophic weather shocks can trigger destructive coping responses to disaster—for example, withdrawal of children from school, distress sale of assets, refugee migration, crime, and severe human suffering. Moreover, these adverse impacts often persist as children's physical growth falters, and household productivity, asset accumulation, and income growth are dampened (Dercon and Krishnan 2000; Hoddinott and Kinsey 2001; Hoddinott 2006). The prospect of such shocks may also induce underinvestment in assets at risk, limiting poor households' ability to grow their way out of poverty over time (Carter and Barrett 2006). The problem originates with the difficulty poor households face in insuring covariate risk. While informal social insurance arrangements and flexible credit contracts often provide the poor with significant insurance against household-specific, idiosyncratic risk, when entire communities or social networks confront the same biophysical shock, their capacity to buffer members' welfare may be insufficient to prevent severe and widespread human suffering. The magnitude and intensity of such suffering sometimes merits the label "famine" (Howe and Devereux 2004). External (domestic and international) relief organizations and governments commonly step in to provide emergency assistance in the wake of catastrophic covariate shocks such as drought, especially when the specter of famine looms. Operational agencies and the donor community are thereby financially exposed to catastrophic weather risks in developing countries via their humanitarian commitment to emergency response. In addition to their potential for other purposes (Barnett, Barrett and Skees forthcoming; Alderman and Haque 2007), recent innovations in index insurance show promise as a means to facilitate improved emergency response to weather-related catastrophic shocks that threaten famine. Just as improved early warning systems and emergency needs assessment practices have used timely monitoring and analysis of vulnerable areas to significantly improve humanitarian response in recent decades (Barrett and Maxwell 2005), so too can weather index insurance facilitate further improvement by addressing several key remaining weaknesses in global famine prevention efforts. This paper briefly outlines how donors and operational agencies might use weather index insurance for famine prevention, enumerates key prospective benefits from such products, and then illustrates the possibilities with an application to the arid lands of northern Kenya, an area of recurring severe droughts that elicit massive international humanitarian responses.